1996
DOI: 10.1111/j.1365-2133.1996.tb01497.x
|View full text |Cite
|
Sign up to set email alerts
|

Both psoriasis and benign migratory glossitis are associated with HLA-Cw6

Abstract: This study was undertaken to investigate human leucocyte antigen (HLA) associations with benign migratory glossitis and psoriasis in Brazilian patients and particularly to determine whether benign migratory glossitis is also associated with HLA-Cw6, the classical association observed in psoriasis. The results showed a highly significant association of Cw6 with both psoriasis and benign migratory glossitis, with this antigen being present in 59.1% of the patients with psoriasis, in 43.8% of the patients with be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Over the past few years an association between geographic tongue, fissured tongue and psoriasis has been postulated. Some authors believe that it is a natural developmental anomaly and a coincidence finding [46,49] while others suggest a pathogenic relation between them [50]. …”
Section: Discussionmentioning
confidence: 99%
“…Over the past few years an association between geographic tongue, fissured tongue and psoriasis has been postulated. Some authors believe that it is a natural developmental anomaly and a coincidence finding [46,49] while others suggest a pathogenic relation between them [50]. …”
Section: Discussionmentioning
confidence: 99%
“…While recent studies have suggested that GT may manifest as an early oral marker of psoriasis onset and severity [ 4 , 5 , 8 ], it should be included in the criteria for the disease’s diagnostic, as well as its therapeutic definition, highlighting the importance of careful evaluation of GT by different healthcare professionals [ 10 , 11 , 12 ]. Because these reports indicate that GT is a potential oral manifestation of psoriasis ( Table 1 ), the geographic tongue area and severity index (GTASI) was developed and proposed, based on cumulative clinical data and experts’ recommendations.…”
Section: Introductionmentioning
confidence: 99%